KONSTRUKSI CITRA DIRI DAN FENOMENA DRAMATURGI MELALUI MEDIA SOSIAL INSTAGRAM DI KOTA PEKANBARU - Nila Rianti; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Instagram as one of the social media, makes easy for everyone to have social interactions. In interacting, everyone certainly displays the image to others. As well as using Instagram, aside from being a medium for communicating or as an entertainment medium, Instagram can also be a medium for constructing a self-immage from the users. Self Immage that displayed on Instagram, of course prepared with careful planning. For the sake of making a good immage, Instagram users are willing to pay quite a lot for the sake of being seen on their Instagram. The immage thats constructed also has various meanings. However, there are differences between the appereance of Instagram and the reality of life from the Instagram users. So thats raises a dramaturgy phenomenon. This research aims to find out and analyze the process of constructing self-immage on the subject and knowing the meaning of self-immage that owned by subject. This research uses dramaturgy theory, self-immage and consumptive society and also self-actualization. The research subject is Instagram users in the city of Pekanbaru who were consistent in using a particular hashtag in caption when uploading photos or videos and their Instagram not a private account. This research uses the technique of determining subjects with certain criteria (purposive). This type of research is qualitative, with data collection techniques obtained by observation, in-depth interviews and documentation. The result of this research show that there is a process in constructing self-immage on Instagram, and then all subjects have the same pattern, namely perfecting the back stage so the immage looks good on the front stage (their Instagram). The meaning of the immage that is built is as self existence, self actualization and economic meaning.  Keywords: Instagram, self-immage and dramaturgy.